A New Perspective of Trees Competition Network Research - Wang Shaohua; Yang Ting; Ouyang shengxiang (E3S Web of Conferences, 2024)
Forest competition is a key factor driving forest dynamics and stand structure, and is one of the core issues in ecological research. Competition is a complex ecological process with temporal changes, which is interrelated and affected with forest growth, stand structure dynamics and environmental changes. Although there have been many researches on competition, tree growth, stand structure and climate, the interactions among trees have been studied by static competition index measurement, which usually lacks temporal variation related to natural forest development and environmental conditions, and the response mechanism and related theory of competition to stand development and environmental fluctuation have been studied insufficiently.(2) Single tree competition index model;(3) Interaction between tree competition and tree growth, stand structure and environment;(4) Tree competition based on complex network. Finally, according to the complex interaction of tree competition, the research strategy of tree competition network structure with “single tree” as node and “single tree competition relationship” as edge is discussed, in order to provide reference for the study of tree interaction and forest ecosystem dynamics.